Innate cell profiles during the acute and convalescent phase of SARS-CoV-2 infection in children - Melanie R. Neeland (Nature Portfolio, 2021)
Childhood infection with SARS CoV2 is associated with a milder course of infection but the immunopathogenesis of this remains unclear. Here the authors explore immunological differences in the innate immune system during acute and convalescent SARS CoV2 infection in the young.